2016
DOI: 10.1021/acs.analchem.6b04191
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework Nanomaterials as Novel Signal Probes for Electron Transfer Mediated Ultrasensitive Electrochemical Immunoassay

Abstract: A novel and simple electrochemical immunoassay for C-reactive protein was developed using metal-organic frameworks (Au-MOFs) as signal unit. In this study, we found MOFs could be used as signal probe. And this new class of signal probe differs from traditional probe. The signal of the copper ions (Cu) from MOFs could be directly detected without acid dissolution and preconcentration, which would greatly simplify the detection steps and reduce the detection time. Moreover, MOFs contain large amounts of Cu ions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(47 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…The results indicated that our fluxgate sensing system is highly sensitive and has a wider linear range when compared with those in recently reported studies. Conversely, the detection limits of a reported photothermal system (PTB) [ 32 ], and a metal-organic framework nanomaterials-based (MOF) electrochemical immunoassay (ECL) technique [ 33 ], or the Molybdenum-disulfide-polyaniline-gold nanoparticles (MoS 2 -PANI-GNPs)-based immunosensor [ 34 ], were significantly lower than that in the current study. However, the PTB sensing technique is based on the photothermal effect, and it therefore needs to be performed under strict temperature monitoring.…”
Section: Resultsmentioning
confidence: 70%
“…The results indicated that our fluxgate sensing system is highly sensitive and has a wider linear range when compared with those in recently reported studies. Conversely, the detection limits of a reported photothermal system (PTB) [ 32 ], and a metal-organic framework nanomaterials-based (MOF) electrochemical immunoassay (ECL) technique [ 33 ], or the Molybdenum-disulfide-polyaniline-gold nanoparticles (MoS 2 -PANI-GNPs)-based immunosensor [ 34 ], were significantly lower than that in the current study. However, the PTB sensing technique is based on the photothermal effect, and it therefore needs to be performed under strict temperature monitoring.…”
Section: Resultsmentioning
confidence: 70%
“…[17][18] In addition, the metal ions are bonded to the organic linkers, which are more stable than the free ions. [19] Based on the above advantages, Cu-MOF has been used by researchers to construct electrochemical sensors for the detection of H 2 O 2 , [20] glucose, [21] DNA [8] and diethylstilbestrol. [22] For example, Ling et al [8] designed a sensitive electrochemical DNA detection sensor based on Cu-MOF and allosteric switch of hairpin DNA to achieve highly sensitive detection of target DNA strands.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 17‐18 ] In addition, the metal ions are bonded to the organic linkers, which are more stable than the free ions. [ 19 ] Based on the above advantages, Cu‐MOF has been used by researchers to construct electrochemical sensors for the detection of H 2 O 2 , [ 20 ] glucose, [ 21 ] DNA [ 8 ] and diethylstilbestrol. [ 22 ] For example, Ling et al .…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…By the use of Cu‐MOF nanomaterials as novel signal probes, a simple electrochemical immunoassay for C‐reactive protein was developed, as shown in Figure . Signal antibody‐modified AuNPs‐MOF composite, in which the antibodies, Cu‐MOFs, AuNPs acted as a complexing agent for recognition layer, a signal probe, and a sensitive promoter, respectively, was constructed for fabrication of the electrochemical sensor.…”
Section: Electrochemical Sandwich Assays Using Mofs As Outer Probesmentioning
confidence: 99%